2014
DOI: 10.1007/s12663-014-0666-0
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical Evaluation of the Effects of Chlorhexidine, Warm Saline Mouth Washes and Microbial Growth on Intraoral Sutures

Abstract: Introduction Post operative care of sutured wound is important after surgery. Sutured wounds within the oral cavity are kept clean through frequent rinses with either normal saline, chlorhexidine mouth rinses, hydrogen peroxide diluted with saline, or fresh tap water. Patients and Methods The patients were randomised into 3 groups (A, B and C). The container used had 34 chlorhexidine, 34 warm saline and 32 warm water mouth rinses. The latter served as control. All selected patients had scaling and polishing do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The inability to carry out anaerobic culture in our center has a negative influence on our results, and this challenge has been previously highlighted 12 . S. pyogenese and S. aureus have been previously isolated in our environment 17 21 and were found in microbial cultures in the present study. In odontogenic infection, a whole variety of microorganisms can be identified, many of which are not culturable using standard methods 22 .…”
Section: Discussionsupporting
confidence: 61%
“…The inability to carry out anaerobic culture in our center has a negative influence on our results, and this challenge has been previously highlighted 12 . S. pyogenese and S. aureus have been previously isolated in our environment 17 21 and were found in microbial cultures in the present study. In odontogenic infection, a whole variety of microorganisms can be identified, many of which are not culturable using standard methods 22 .…”
Section: Discussionsupporting
confidence: 61%
“…A study done by Fomete et al showed that warm saline mouth wash had no significant effects on bacterial growth. (Fomete et al, 2015) However, Listerine mouth wash showed contradictory results in a study conducted by Okuda et al (1998) as Listerine is an antimicrobial mouth rinse it eliminates a wide range of bacteria from the oral cavity in 10 to 30 seconds. (Okuda et al, 1998)A clinical trial comparing five different mouth rinses showed that triclosan and essential oil mouth rinses increased the salivary pH immediately after their use.…”
Section: Discussionmentioning
confidence: 99%
“…Salt water gargling is still commonly used and is considered one of the best and safest treatments for cough [24]. Salt water gargling, containing up to 3.4% NaCl, is found to be even more effective than antibiotics or analgesics for dental infections [25], sore throat, and wound healing, compared to chlorhexidine [26]. The results of this study show that in the CP group, although spraying saline solution on the throat is relatively effective in providing symptomatic relief, the improvements are only short-lasting and incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all systemic drugs induce side effects and cause more harm than good, whereas topically applying any chemical on the LRT would block the healing of damaged URT mucosa [28]. Taking into consideration the future research on mono-target anticough drugs, multiple side effects [29,30], development of bacterial resistance and inefficacy of antibiotics for the treatment of dry cough [31,32], F-VB-Gy opens a totally new horizon not only for the treatment of dry or wet cough, but potentially also for the treatment of other topical diseases having a multifactorial origin [33][34][35]. Further research is required to use this non-invasive technology for the treatment of other topical diseases for which there is still no effective treatment available.…”
Section: Discussionmentioning
confidence: 99%